Religiosity and desistance from drug use - Chu, Doris C. (Criminal justice and behavior, 2007)
Recent research acknowledges an inverse relationship between religiosity and crime (though some claim it is a modest one), but no desistance theories to date include religiosity in their model to help explain desistance from drug use. A better understanding of how religiosity is related to the initiation of and desistance from drug use can lead to more effective preventive and rehabilitative interventions. Data derived from Wave 5 to Wave 7 of the National Youth Survey are employed to test whether religiosity exerts an effect on initiation of and desistance from drug use. The findings suggest religious behavior has a direct effect on individuals' desistance from marijuana and hard-drug use. On the other hand, religious salience has a significant deterrent effect only on the onset of drug use; it does not have a significant effect on individuals' desistance from drugs. Policy implications are discussed, and future research suggestions are offered.